Experimental study of rainfall intensity on silty sand slope - Jelani, Jestin; Suif, Zuliziana; Ahmad, Nordila; Muhammad Sadiq Rabbani, Muhammad Jazil Rabbani; Khairulazman, Nurul Afiffah (Universitas Mercu Buana, 2025)
Malaysia, located in the tropical region, is blessed with an abundance of rainfall, particularly during the monsoon season. Previous studies have shown that major landslide occurrences in Malaysia are primarily caused by frequent and prolonged rainfall. This study is conducted to investigate the effect of different rainfall intensities on the silty sandy slope through a small-scale slope model. The soil samples were collected from Bukit Tabur, Kuala Lumpur, Malaysia, to construct a 60° slope model. A continuous rainfall intensity of 50, 100, and 150 mm/hour was considered in the study to determine the type and duration of failure. Two cameras were positioned at the front and side of the slope model to capture the elapsed time since the onset of rainfall. The gullies failures were observed in all experiments. It is due to the soil on the slope surface reaching nearly full saturation, causing runoff water to move down the slope and drain downstream, resulting in surface erosion. Such a failure mechanism agreed well with the failures (formed gullies) recorded on the downstream slope of the Bukit Tabor after high-intensity rainfalls. The time of failure for different rainfall intensities was compared to the highest rainfall intensity. The duration of slope failure for 50 mm/hr and 100 mm/hr is approximately 30% and 5% slower than that of rainfall intensity at 150 mm/hr. The results suggest that the slope is more prone to failure with higher rainfall intensities.